2017
DOI: 10.1016/j.ijscr.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Case report on the non-operative management of a retrievable inferior vena cava filter perforating the duodenum

Abstract: HighlightsIVC filters as an alternative to anticoagulation therapy carry their own risks.IVC filters may erode into surrounding structures.Duodenal perforation by a retrievable IVC filter is a rare and serious complication.Caval enteric perforation by retrievable IVC filter can be managed non-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although the incidence of perforation of the IVC wall is 0.2% in patients undergoing IVC filter placement [4], the actual incidence of duodenal perforation is unknown. From 1972 to 2017, only 25 cases similar to our case have been reported [3, 58]. Herein, we report a very case of duodenal penetration by an IVC filter strut after retroperitoneal lymph node dissection (RPLND).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Although the incidence of perforation of the IVC wall is 0.2% in patients undergoing IVC filter placement [4], the actual incidence of duodenal perforation is unknown. From 1972 to 2017, only 25 cases similar to our case have been reported [3, 58]. Herein, we report a very case of duodenal penetration by an IVC filter strut after retroperitoneal lymph node dissection (RPLND).…”
Section: Introductionmentioning
confidence: 59%
“…It is still controversial whether repair of a penetration site in the duodenum is necessary. Although we repaired duodenal penetration by EGD clipping in the present case, duodenal penetration was not repaired in another report with an endovascular IVC retrieval [8]. However, a systematic review revealed that 23.8% of patients (5/21) with duodenal perforation by an IVC filter had symptoms of gastrointestinal bleeding, and 66.7% of patients (14/21) underwent repair of the duodenum [3].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, the implanting of temporary IVCF does not meet the requirement to reduce the risk of PE. To overcome the shortcomings of temporary IVCF, retrievable IVCF was produced …”
Section: Introductionmentioning
confidence: 99%